Gallate-based metalâorganic frameworks, a new family of hybrid materials and their applications: A review - Ismail, M. (MDPI AG, 2020)
Within three decades of fundamental findings in research on metalâorganic frameworks (MOFs), a new family of hybrid materials known as gallate-based MOFs, consisting of metal salt and gallic acid, have been of great interest. Due to the fact that gallic acid is acknowledged to display a range of bioactivities, gallate-based MOFs have been initially expended in biomedical applications. Recently, gallate-based MOFs have been gradually acting as new alternative materials in chemical industrial applications, in which they were first reported for the adsorptive separation of light hydrocarbon separations. However, to date, none of them have been related to CO2/CH4 separation. These porous materials have a bright future and can be kept in development for variety of applications in order to be applied in real industrial practices. Therefore, this circumstance creates a new opportunity to concentrate more on studies in CO2 /CH4 applications by using porous material gallate-based MOFs. This review includes the description of recent gallate-based MOFs that presented remarkable properties in biomedical areas and gas adsorption and separation, as well as their future potential application. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.